Evolving the Physical Global Ocean Observing System for Research and Application Services Through International Coordination - Sloyan, Bernadette M.; Wilkin, John; Hill, Katherine Louise; Chidichimo, Maria Paz; Cronin, Meghan F.; Johannessen, Johnny A.; Karstensen, Johannes; Krug, Marjolaine; Lee, Tong; Oka, Eitarou; Palmer, Matthew D.; Rabe, Benjamin; et al. (Frontiers in Marine Science, 2019)
Climate change and variability are major societal challenges, and the ocean is an integral part of this complex and variable system. Key to the understanding of the ocean’s role in the Earth’s climate system is the study of ocean and sea-ice physical processes, including its interactions with the atmosphere, cryosphere, land, and biosphere. These processes include those linked to ocean circulation; the storage and redistribution of heat, carbon, salt and other water properties; and air-sea exchanges of heat, momentum, freshwater, carbon, and other gasses. Measurements of ocean physics variables are fundamental to reliable earth prediction systems for a range of applications and users. In addition, knowledge of the physical environment is fundamental to growing understanding of the ocean’s biogeochemistry and biological/ecosystem variability and function. Through the progress from OceanObs’99 to OceanObs’09, the ocean observing system has evolved from a platform centric perspective to an integrated observing system. The challenge now is for the observing system to evolve to respond to an increasingly diverse end user group. The Ocean Observations Physics and Climate panel (OOPC), formed in 1995, has undertaken many activities that led to observing system-related agreements. Here, OOPC will explore the opportunities and challenges for the development of a fit-for-purpose, sustained and prioritized ocean observing system, focusing on physical variables that maximize support for fundamental research, climate monitoring, forecasting on different timescales, and society. OOPC recommendations are guided by the Framework for Ocean Observing which emphasizes identifying user requirements by considering time and space scales of the Essential Ocean Variables. This approach provides a framework for reviewing the adequacy of the observing system, looking for synergies in delivering an integrated observing system for a range of applications and focusing innovation in areas where existing technologies do not meet these requirements.